Analysis of Ground Movement during Large-Scale Pipe Roof Installation and Artificial Ground Freezing of Gongbei Tunnel - Xiao-qi Zhou; Jian-li Pan; Yang Liu; Cai-cheng Yu (Advances in Civil Engineering, 2021)
This paper analyzes the vertical ground movement during large-scale pipe roof installation and artificial ground freezing of Gongbei tunnel of the Hong Kong-Zhuhai-Macau bridge project. The transverse ground settlement during pipe roof installation is analyzed. The ground loss volume ratio and settlement trough width coefficient during pipe jacking are estimated based on the field measurement of ground settlement. The interaction of pipes during multiple jacking is investigated. The effect of frost heave control by pregrouting, limiting frozen soil thickness, and combination of the two methods is evaluated. The analysis shows that the ground settlement during pipe roof installation by jacking 37 pieces of 1620 mm steel pipes is relatively small with a maximum value of 2.2 cm. The reinforcement to ground provided by the fore-jacked pipes reduces the ground loss volume ratio and, consequently, the ground settlement during the follow-up pipe jacking. The artificial ground freezing generates a relatively large ground heave with a maximum value of 7.8 cm. Pregrouting plays a critical role in the frost heave control by reducing the heave by about 33%. Limiting the frozen soil thickness by heating pipes serves as an effective supplement to frost heave control by reducing the heave by about 9%. The combination of the two measures reduces the ground heave by about 42%. Findings from this paper provide valuable reference to the tunnel construction using pipe roof and artificial ground freezing as presupport.